2015
DOI: 10.1515/jmsp-2014-0042
|View full text |Cite
|
Sign up to set email alerts
|

Control of Slag-Dragging Effects at the Metal–Slag Interface through Electromagnetic Brake in a Slab Mold

Abstract: Turbulent flow when steel is delivered through a nozzle in a slab mold induces dragging forces at the metal-slag interface that entrain slag droplets into the metal bulk. These dragging effects are discontinuous and correspond to the velocity fluctuations of turbulence at that interface which themselves, are dependent on nozzle immersion, nozzle design, mold width and casting speed. Slag viscosity and density, metal viscosity and slag layer thickness are employed to estimate that critical velocity which is emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Particularly critical is the steel flow in the meniscus region where the first solidification of the steel shell takes place, and the lack of flux lubrication combined with surface depressions leads to longitudinal cracks in the cast slab. 1 As reported [2][3][4][5] , nozzle design is very influential on fluid flow phenomena in the mould and in the meniscus in particular. However, the slide or valve gate originally conceived to control primarily the steel throughput is also very important for flow turbulence generation in the mould.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Particularly critical is the steel flow in the meniscus region where the first solidification of the steel shell takes place, and the lack of flux lubrication combined with surface depressions leads to longitudinal cracks in the cast slab. 1 As reported [2][3][4][5] , nozzle design is very influential on fluid flow phenomena in the mould and in the meniscus in particular. However, the slide or valve gate originally conceived to control primarily the steel throughput is also very important for flow turbulence generation in the mould.…”
Section: Introductionmentioning
confidence: 89%
“…10 Other approach is the redesign of the bottom wall of the UTN by making it curved to improve the flow through the gate and later through the nozzle. 11 Actually, right choice of nozzle design, 12 flux chemistry [3][4][5] and control device of steel throughput constitute the essential triade for a successful casting. The present work studies single/phase flows of liquid steel in a slab mould fed through a slide gate device and a pyramid-bottom nozzle, under current operation in a U.S. caster, making emphasis on timedependent flows using water modelling and computer fluid dynamics (CFD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [12] found that the SRF is generated under the conditions of large gas injection, small SEN submergence depth, and low casting speed using water modeling. Using PIV, ultrasound velocimetry (UV) and computational fluid dynamics (CFD) simulation, Ramos et al [17,18] demonstrated that shallow SEN submergence depth is beneficial to form SRF, which tends to induce unstable meniscus fluctuation. Asad et al [19] showed that reduction of the casting speed leads to a decrease in the mean wave amplitude on the mold surface, and the presence of the SRF leads to the occurrence of large-scale standing waves by use of Unsteady Reynolds Average Navier-Stokes (URANS) modeling.…”
Section: Introductionmentioning
confidence: 99%